PENGEMBANGAN MEDIA PEMBELAJAN PAPAN ULAR TANGGA AKSARA JAWA (PALU ANDHA AJA) UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA JAWA KELAS V - Dinarum Osi Fardani; Rosalia Susila Purwanti; Dhiniaty Gularso (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this research and development wasto reveal the quality of the learning media (PALU ANDHA AJA) developed in this study andto know the increase on students’ interest and learning achievement. This research was targeted on Javanese language subject through the implementation of snake and ladder learning media (PALU ANDHA AJA) for grade V students at SD Negeri 1 Banjararjo Ayah Kebumen. The method of this study was Research and Development including: (1) analyzing the potential and problems, (2) collecting data, (3) designing the product, (4)validating the design, (5) revising the design, (6) testing the  product, (7) revising the product, (8) conducting field test, and (9) revising the product. The results of pretest and posttest indicated that there was an increase in the learning of Javanese language through the implementation of PALU ANDHA AJA. Moreover,the result of paired sample t test showeda significance value 0,000 (0,000 <0,05); thus, it could be concluded that there was a significant difference on the students’ learning interest and achievement before and after learning by using PALU ANDHA AJA.